Analyzing the duration frequency and severity of drought using copula function in the Yazd city. Issue 1 (1st September 2021) - EskandariPour, Mehrtash; Soltaninia, Shahrokh
Abstract: Duration and severity are the two main variables used in drought analysis. The copula functions are appropriate for multivariate drought analysis, as it lacks the limitations of the classical multivariate distribution function. This study investigated the bivariate frequency analysis of drought duration and severity of Yazd city in Iran synoptic station during 1953–2013. To this end, first, the drought duration and severity variables were derived from the 6-month Standardized Precipitation Index. Then, considering the distribution functions, the gamma distribution function was selected for analyzing the severity and the exponential distribution function was selected for analyzing the duration and then the Clayton copula function was selected out of the three copula functions as the most appropriate one. After conducting bivariate frequency analysis, the joint seasonal and conjunctive return period and conditional return period curves were plotted. The current study well signified that multivariate analyses could present better interpretations of the reality; for example, as it was identified in conditional return period curves of the drought, for every constant duration, the amount of the return period changed as the severity changed. On the contrary, in analyzing the univariate of duration, no effects of severity were observed. HIGHLIGHTS: Use of multivariate analysis in research due to the high degree of correlation between the severity and duration of drought. Accurate study of the correlation between the two parameters of hardness and duration of drought. Using copula functions in this study that removes the limitations of classical distribution functions. Calculation of 6 months. Estimation of the parameters of the coupling function.